Dispersant, positive electrode slurry and secondary battery thereof
By using dispersants of polymer segments and anchoring groups, the van der Waals gravity between lithium iron phosphate and conductive agent particles is overcome, and the problems of low solid content of the positive electrode slurry and easy cracking of the coating are solved, achieving higher solid content and better coating yield.
Patent Information
- Application Number
- CN202411442383.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The specific surface area of lithium iron phosphate particles is large, resulting in low solid content of the positive electrode slurry and easy cracking on coating, which affects production efficiency and yield.
Using a dispersant, including polymer segments and anchor groups, the van der Waals gravity between lithium iron phosphate and conductive agent particles is overcome by polymer segments, thereby increasing the solid content and coating yield of the cathode slurry.
The solid content of the positive electrode slurry is improved, the coating yield is improved, and the peeling force of the positive electrode sheet and the circulation performance of the battery are enhanced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a dispersant, a positive electrode slurry and a secondary battery thereof. Background Art
[0002] Secondary batteries have the advantages of high voltage, high specific energy, stable discharge voltage, good cycle performance, good safety performance and long service life. They are widely used in power vehicles, energy storage and other fields.
[0003] Lithium-ion batteries in secondary batteries include lithium iron phosphate systems. The specific surface area of material particles in the lithium iron phosphate system is large, and more conductive agents and binders are required, which results in a lower solid content when the slurry reaches a coating viscosity. However, when the solid content in the slurry is high, the coating viscosity increases, which is not conducive to the coating of the slurry, further resulting in a decrease in coating speed, affecting production efficiency. At the same time, low-solid slurry is prone to cracking during coating, reducing the coating yield. Summary of the invention
[0004] The technical problem to be solved by the present invention is to solve the problem of low solid content of positive electrode slurry and easy cracking during coating due to the large specific surface area of lithium iron phosphate particles. The present invention provides a dispersant, positive electrode slurry and a secondary battery thereof.
[0005] In order to solve the above technical problems, the present invention provides a dispersant, which includes a polymer segment and an anchoring group, wherein the polymer segment includes an acrylate-polyol unit, and the anchoring group includes one or more of a nitrile group, an amide group, an ester group, a carboxyl group and a hydroxyl group.
[0006] Preferably, the terminal group of the polymer chain segment is an acrylate group.
[0007] Preferably, the dispersant is obtained by reacting a raw material composition comprising an acrylate-polyol monomer and a monomer containing an anchor group.
[0008] Preferably, the mass ratio of the anchor group-containing monomer to the acrylate-polyol monomer is (10-50):(30-90).
[0009] Preferably, the acrylate-polyol monomer contains two or more acrylate groups, and / or the anchor group-containing monomer contains one or more of a nitrile group, an amide group, an ester group, a carboxyl group and a hydroxyl group.
[0010] Preferably, the acrylate-polyol monomers include one or more of poly(ethylene glycol) diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, and poly(propylene glycol) dimethacrylate;
[0011] And / or, the anchor group-containing monomer includes one or more of acrylonitrile, methacrylonitrile, acrylamide, bisacrylamide, cyanoacetamide, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, lauryl acrylate, isobutyl acrylate, tert-butyl acrylate, octadecyl acrylate, phenyl methacrylate, n-hexyl acrylate, stearyl methacrylate, ethylene glycol, and ethylene glycol monomethyl ether.
[0012] Preferably, the molecular weight of the dispersant is 2000-30000 g / mol.
[0013] In a second aspect, the present application provides a positive electrode slurry, comprising a positive electrode active material, a conductive agent and a dispersant as described in any one of the above.
[0014] Preferably, the surface of the positive electrode active material is modified with a silane coupling agent containing double bonds;
[0015] And / or, the surface of the conductive agent is modified with a silane coupling agent containing double bonds;
[0016] And / or, the silane coupling agent containing a double bond includes one or more of (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane, 3-(trimethoxysilyl)propyl acrylate, vinyltrimethoxysilane, and allyltrimethoxysilane.
[0017] In a third aspect, the present application provides a secondary battery, comprising a negative electrode sheet, an electrolyte and a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode material layer arranged on at least one side surface of the positive electrode collector, and the positive electrode material layer is prepared from the positive electrode slurry as described above.
[0018] On the one hand, the dispersant provided in the present application has a polymer chain segment and an anchoring group, which overcomes the van der Waals attraction between lithium iron phosphate and the conductive agent particles through the polymer chain segment, reduces the viscosity effect brought by the conductive agent, thereby increasing the solid content of the positive electrode slurry and improving the coating yield.
[0019] In particular, the structure of the dispersant provided in the present application has an end group that is an acrylate group. The acrylate group at the end of the dispersant can improve the cohesive force of the coating formed by the positive electrode slurry by self-polymerization or by reacting with other double-bonded groups in the positive electrode slurry (such as double bonds in a silane coupling agent containing double bonds), thereby further improving the peeling force.
[0020] Secondly, the positive electrode slurry of the present application contains the above-mentioned dispersant, which overcomes the van der Waals attraction between the positive electrode active material and the conductive agent particles, reduces the viscosity effect brought by the conductive agent, thereby increasing the solid content of the positive electrode slurry and improving the coating yield. DETAILED DESCRIPTION
[0021] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0022] An embodiment of the present application provides a dispersant, which includes a polymer segment and an anchoring group, wherein the polymer segment includes an acrylate-polyol unit, and the anchoring group includes one or more of a nitrile group, an amide group, an ester group, a carboxyl group, and a hydroxyl group.
[0023] The dispersant provided in the present application has a polymer segment and an anchoring group, which overcomes the van der Waals attraction between lithium iron phosphate and conductive agent particles through the polymer segment, reduces the viscosity effect of the conductive agent, thereby increasing the solid content of the positive electrode slurry and improving the coating yield. The dispersant provided in the present application contains an acrylate group, which can increase the cohesion of the coating formed by the positive electrode slurry through self-polymerization or interaction with other double-bonded groups in the positive electrode slurry, and further increase the peeling force of the positive electrode sheet.
[0024] Preferably, the terminal group of the polymer chain segment is an acrylate group.
[0025] In some embodiments, the dispersant is obtained by reacting a raw material composition comprising an acrylate-polyol monomer and an anchor group-containing monomer.
[0026] Preferably, the acrylate-polyol monomer contains two or more acrylate groups.
[0027] Specifically, the acrylate-polyol monomer has acrylate groups at both ends, wherein the acrylate group at one end reacts with the anchor group monomer, and the acrylate group at the other end can be used for self-polymerization and to react with lithium iron phosphate / conductive agent modified by a double bond-containing silane coupling agent.
[0028] In some embodiments, the mass ratio of the anchor group-containing monomer to the acrylate-polyol monomer is (10-50): (30-90).
[0029] Specifically, the mass ratio of the anchor group-containing monomer to the acrylate-polyol monomer includes, but is not limited to, 10:30, 50:90, 25:50, 20:30, 50:50 or 50:80.
[0030] In some embodiments, the acrylate-polyol monomers include one or more of poly(ethylene glycol) diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, and poly(propylene glycol) dimethacrylate. By selecting the above-mentioned acrylate-polyol monomers, it is convenient to control the length and steric hindrance of the polymer chain segments in the dispersant, thereby adjusting the dispersion effect.
[0031] In a preferred embodiment, the molecular weight of the acrylate-polyol monomer is 300-15000 g / mol.
[0032] In some embodiments, the anchoring group-containing monomer includes one or more of acrylonitrile, methacrylonitrile, acrylamide, bisacrylamide, cyanoacetamide, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, lauryl acrylate, isobutyl acrylate, tert-butyl acrylate, octadecyl acrylate, phenyl methacrylate, n-hexyl acrylate, stearyl methacrylate, ethylene glycol, and ethylene glycol monomethyl ether. By introducing the above-mentioned anchoring group into the structure of the dispersant, the anchoring group is easily combined with the hydroxyl group on the treated aluminum foil, thereby increasing the bonding strength between the coating formed by the positive electrode slurry and the aluminum foil, and enhancing the peeling strength between the coating and the aluminum foil.
[0033] Furthermore, the dispersant can be obtained by conventional double bond polymerization reaction, and the specific reaction conditions are easily known to those skilled in the art. For example, the preparation method includes the following steps:
[0034] Mix ethanol as a solvent, an anchor group-containing monomer, and an acrylate-polyol monomer under nitrogen, and stir to obtain a mixed solution;
[0035] The mixed solution was heated to 50-80° C. under a nitrogen atmosphere, and then an initiator, azobisisobutyronitrile, was added, and the mixture was kept warm with continuous stirring. The reaction was stopped after 24 hours of reaction, and then the ethanol was removed by heating and rotary evaporation to obtain a dispersant.
[0036] In some embodiments, the molecular weight of the dispersant is 2000-30000 g / mol. By regulating the molecular weight of the dispersant, the chain length of the polymer segment in the dispersant is regulated to overcome the van der Waals attraction between the LFP and conductive agent SP particles, thereby adjusting the dispersing properties of the dispersant. If the molecular weight of the dispersant is too low, it will not provide a sufficiently thick molecular layer to prevent the aggregation of LFP and conductive agent SP particles, which will lead to a decrease in the dispersion effect and the stability of the slurry. If the molecular weight of the dispersant is too high, the polymer molecules of the dispersant are easy to fold back on themselves, causing the slurry to flocculate.
[0037] In a second aspect, an embodiment of the present application provides a positive electrode slurry, comprising a positive electrode active material, a conductive agent and a dispersant as described in any one of the above embodiments.
[0038] The positive electrode slurry of this embodiment contains the above-mentioned dispersant, which overcomes the van der Waals attraction between the positive electrode active material and the conductive agent particles, reduces the viscosity effect caused by the conductive agent, thereby increasing the solid content of the positive electrode slurry and improving the coating yield.
[0039] Preferably, the surface of the positive electrode active material is modified with a silane coupling agent containing double bonds. Specifically, the positive electrode active material can be various positive electrode active materials commonly used in the art, such as lithium iron phosphate.
[0040] The surface of lithium iron phosphate is modified with a silane coupling agent containing double bonds, so that the double bonds on the surface of the modified lithium iron phosphate react with the dispersant, ensuring that the modified lithium iron phosphate and the dispersant achieve the dispersion stability of the positive electrode slurry through steric hindrance, anchoring functional groups and the like, thereby increasing the solid content of the positive electrode slurry. At the same time, the modified lithium iron phosphate is combined with the dispersant to enhance the cohesion of the coating formed by the positive electrode slurry.
[0041] In the present invention, the surface of the conductive agent is modified with a silane coupling agent containing double bonds. The conductive agent can be any conductive agent commonly used in the art, for example, conductive carbon black.
[0042] When the molecular weight of the dispersant is 2000~10000 g / mol, the chemical bonds of the anchoring functional groups in the dispersant and the interaction between the double bonds of the polymer chain segments and the lithium iron phosphate modified by the double-bond silane coupling agent play the main dispersing effect. In the preparation process of the positive electrode slurry, it is necessary to first add lithium iron phosphate (LFP) modified by the double-bond silane coupling agent, so that the dispersant is first coated on the surface of LFP and then add the conductive carbon black (SP) modified by the double-bond silane coupling agent.
[0043] When the molecular weight of the dispersant is between 20,000 and 30,000 g / mol, the steric hindrance of the dispersant plays a role. It is necessary to first add small-particle SP modified by a double-bond silane coupling agent, so that the dispersant is first coated on the SP surface and then add LFP modified by a double-bond silane coupling agent.
[0044] When the molecular weight of the dispersant is between 10,000 and 20,000 g / mol, LFP and SP can be added simultaneously and both are modified by a silane coupling agent containing a double bond. At this time, the steric hindrance of the polymer chain segments, the chemical bonds of the anchoring functional groups, and the interaction between the double bonds of the polymer chain segments and LFP and SP modified by a silane coupling agent containing a double bond play the main dispersing effect.
[0045] In some embodiments, the silane coupling agent containing a double bond includes one or more of (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane, 3-(trimethoxysilyl)propyl acrylate, vinyltrimethoxysilane, and allyltrimethoxysilane.
[0046] In the present invention, the method for obtaining the lithium iron phosphate and the conductive agent whose surface is modified with a silane coupling agent containing a double bond is well known to those skilled in the art. For example, they can be directly purchased or prepared by themselves. Furthermore, the method for modifying the lithium iron phosphate and the conductive agent with a silane coupling agent containing a double bond is as follows:
[0047] NMP (N-methylpyrrolidone) as a solvent is mixed with a silane coupling agent containing a double bond, and stirred to obtain a mixed solution. LFP is added to the mixed solution, and after pre-mixing, it is dispersed at a high speed to obtain LFP modified with a silane coupling agent containing a double bond.
[0048] NMP as a solvent and a silane coupling agent containing a double bond are mixed and stirred to obtain a mixed solution, SP is added to the mixed solution, and after pre-mixing, the SP modified with a silane coupling agent containing a double bond is dispersed at a high speed to obtain the SP.
[0049] In some embodiments, the positive electrode slurry includes the following components by weight: 94-97.5 parts of positive electrode active material, 0.8-2 parts of conductive agent, 0.1-0.3 parts of dispersant, 0.1-0.3 parts of silane coupling agent, and 1.5-3 parts of binder. The binder may be a common positive electrode binder in the art, such as polyvinylidene fluoride (PVDF). The silane coupling agent is preferably the aforementioned silane coupling agent containing double bonds.
[0050] It should be noted that the sum of all the components in the above weight components is not necessarily equal to 100 parts, and the above weight parts are the mass ratios between the components.
[0051] In a third aspect, an embodiment of the present application provides a secondary battery, comprising a negative electrode sheet, an electrolyte and a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode material layer arranged on at least one side surface of the positive electrode collector, and the positive electrode material layer is prepared from the positive electrode slurry as described above.
[0052] The present invention is further described below by way of examples.
[0053] The dispersant, positive electrode slurry, positive electrode sheet and secondary battery disclosed in the present invention are specifically described.
[0054] Example 1
[0055] Dispersants
[0056] 350 parts of ethanol, 25 parts of acrylonitrile and 50 parts of poly(ethylene glycol) diacrylate were mixed under nitrogen and stirred at a speed of 50 r / min for 30 seconds to obtain a mixed solution;
[0057] The mixed solution was heated to 50°C under a nitrogen atmosphere, and then 1.5 parts of azobisisobutyronitrile were added, the temperature was kept at 50°C, and stirring was continued at a speed of 50 r / min. The reaction was stopped after 24 hours, 250 parts of N-methylpyrrolidone were added to the obtained polymer solution, and the ethanol was removed by heating and rotary evaporation to obtain a dispersant with a molecular weight of 10000~20000 g / mol.
[0058] Cathode slurry
[0059] The positive electrode slurry includes 96 parts of lithium iron phosphate modified with vinyltrimethoxysilane, 1 part of conductive carbon black modified with vinyltrimethoxysilane, 0.2 parts of dispersant, 0.2 parts of vinyltrimethoxysilane, and 2 parts of polyvinylidene fluoride (PVDF).
[0060] A dispersant was added to lithium iron phosphate modified with vinyltrimethoxysilane and conductive carbon black modified with vinyltrimethoxysilane, and vinyltrimethoxysilane and PVDF were added after mixing. After dispersion, a positive electrode slurry was obtained, and the mass solid content of the positive electrode slurry was 65.0%.
[0061] Preparation of positive electrode
[0062] The positive electrode slurry is coated on the two surfaces of the positive electrode current collector Al foil, then dried, and the surface morphology of the electrode sheet is observed (whether it is cracked). After cold pressing, slitting and other processes, the positive electrode sheet is obtained.
[0063] Preparation of negative electrode
[0064] After mixing 1.5% dispersant, 96% negative electrode active material graphite, 1% negative electrode conductive agent conductive carbon black, and 1.5% thickener sodium carboxymethyl cellulose (CMC), deionized water is added and stirred to make negative electrode slurry. Then the negative electrode slurry is coated on both surfaces of the negative electrode current collector Cu foil, and after drying, cold pressing, slitting and other processes, the negative electrode sheet is obtained.
[0065] Secondary battery preparation
[0066] The negative electrode sheet, isolation film (PE film), and positive electrode sheet are stacked in order, with the isolation film placed between the positive and negative electrodes to play an isolating role, to form an electrode assembly, which is placed in an outer package, injected with commercially available electrolyte and packaged, and then subjected to processes such as liquid injection, formation, and exhaust to obtain a secondary battery.
[0067] Example 2
[0068] Most of the steps of Example 2 are the same as those of Example 1, except that the raw material composition of the dispersant includes 90 parts of poly(ethylene glycol) diacrylate and 25 parts of acrylonitrile, and the molecular weight of the dispersant is 20,000-30,000 g / mol.
[0069] The mass solid content of the positive electrode slurry is 65.4%.
[0070] Example 3
[0071] Most of the steps of Example 3 are the same as those of Example 1, except that the raw material composition of the dispersant includes 90 parts of poly(ethylene glycol) diacrylate and 25 parts of acrylonitrile, and the molecular weight of the dispersant is 20,000-30,000 g / mol.
[0072] A dispersant was added to the conductive carbon black modified with vinyltrimethoxysilane, and after mixing, lithium iron phosphate modified with vinyltrimethoxysilane, vinyltrimethoxysilane and PVDF were added to obtain a positive electrode slurry after dispersion. The mass solid content of the positive electrode slurry was 65.5%.
[0073] Example 4
[0074] Most of the steps of Example 4 are the same as those of Example 1, except that the raw material composition of the dispersant includes 30 parts of poly(ethylene glycol) diacrylate and 25 parts of acrylonitrile, and the molecular weight of the dispersant is 2000-10000 g / mol. The mass solid content of the positive electrode slurry is 64.9%.
[0075] Example 5
[0076] Most of the steps of Example 5 are the same as those of Example 1, except that the raw material composition of the dispersant includes 30 parts of poly(ethylene glycol) diacrylate and 25 parts of acrylonitrile, and the molecular weight of the dispersant is 2000-10000 g / mol.
[0077] A dispersant was added to lithium iron phosphate modified with vinyltrimethoxysilane, and conductive carbon black modified with vinyltrimethoxysilane, vinyltrimethoxysilane and PVDF were added after mixing to obtain a positive electrode slurry after dispersion. The mass solid content of the positive electrode slurry was 64.7%.
[0078] Example 6
[0079] Most of the steps of Example 6 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of poly(ethylene glycol) diacrylate and 50 parts of acrylonitrile, and the molecular weight of the dispersant is 10000-20000 g / mol. The mass solid content of the positive electrode slurry is 65.1%.
[0080] Example 7
[0081] Most of the steps of Example 7 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of poly(ethylene glycol) diacrylate and 10 parts of acrylonitrile, and the molecular weight of the dispersant is 10000-20000 g / mol. The mass solid content of the positive electrode slurry is 65.0%.
[0082] Example 8
[0083] Most of the steps of Example 8 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate and 25 parts of acrylamide, and the molecular weight of the dispersant is 10000-20000 g / mol. The lithium iron phosphate is modified by 3-(trimethoxysilyl)propyl acrylate, and the conductive carbon black is modified by 3-(trimethoxysilyl)propyl acrylate. The mass solid content of the positive electrode slurry is 65.1%.
[0084] Example 9
[0085] Most of the steps of Example 9 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate and 25 parts of ethyl acrylate, and the molecular weight of the dispersant is 10000-20000 g / mol. The lithium iron phosphate is modified by allyltrimethoxysilane, and the conductive carbon black is modified by allyltrimethoxysilane. The mass solid content of the positive electrode slurry is 65.1%.
[0086] Example 10
[0087] Most of the steps of Example 10 are the same as those of Example 1, except that the raw material composition of the dispersant includes 100 parts of poly(ethylene glycol) diacrylate and 25 parts of acrylonitrile, and the molecular weight of the dispersant is 35000-40000 g / mol. The mass solid content of the positive electrode slurry is 64.1%.
[0088] Embodiment 11
[0089] Most of the steps of Example 11 are the same as those of Example 1, except that the raw material composition of the dispersant includes 20 parts of poly(ethylene glycol) diacrylate and 25 parts of acrylonitrile, and the molecular weight of the dispersant is 600-1900 g / mol. The mass solid content of the positive electrode slurry is 62.5%.
[0090] Example 12
[0091] Most of the steps of Example 12 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of poly(ethylene glycol) diacrylate and 60 parts of acrylonitrile, and the molecular weight of the dispersant is 10000-20000 g / mol. The mass solid content of the positive electrode slurry is 64.7%.
[0092] Embodiment 13
[0093] Most of the steps of Example 13 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of poly(ethylene glycol) diacrylate and 5 parts of acrylonitrile, and the molecular weight of the dispersant is 10000-20000 g / mol. The mass solid content of the positive electrode slurry is 64.4%.
[0094] Embodiment 14
[0095] Most of the steps of Example 14 are the same as those of Example 1, except that the lithium iron phosphate and the conductive carbon black are not modified by the double-bond-containing silane coupling agent. The mass solid content of the positive electrode slurry is 65.0%.
[0096] Comparative Example 1
[0097] Most of the steps of Comparative Example 1 are the same as those of Example 1, except that the dispersant is poly(ethylene glycol) diacrylate. The mass solid content of the positive electrode slurry is 60.8%.
[0098] Comparative Example 2
[0099] Most of the steps of Comparative Example 2 are the same as those of Example 1, except that the dispersant is poly(ethylene glycol) diacrylate. The lithium iron phosphate and the conductive carbon black are not modified by a double-bond-containing silane coupling agent. The mass solid content of the positive electrode slurry is 60.3%.
[0100] Comparative Example 3
[0101] Comparative Example 3 is similar to Example 1 in most steps, except that the dispersant is polyvinyl pyrrolidone. The mass solid content of the positive electrode slurry is 60.5%.
[0102] Electrical performance test:
[0103] The positive electrode sheets and secondary batteries prepared in the above examples and comparative examples were subjected to the following tests.
[0104] 1) Positive electrode peel strength test:
[0105] After the positive electrode sheet is compacted, a tensile testing machine is used to measure the peel strength of the positive electrode sheet. The test method refers to GB2792-2014.
[0106] 2) Normal temperature cycle test
[0107] The specific method is: let the soft pack battery stand until the temperature reaches 25℃±2℃, test the capacity of the soft pack battery, record it as the capacity before storage, discharge the soft pack battery at 0.5C constant current to 2.7V, charge at 1C constant current to 4.3V, then charge at constant voltage to the cut-off current of 0.05C, and then discharge at 1C constant current to 2.75V after charging; cycle 500 times in this way, and record the capacity retention test results as shown in Table 1 below.
[0108] Table 1
[0109]
[0110] By comparing the test results of Examples 1-14 and Comparative Examples 1-3, it can be seen that the positive electrode sheet obtained by the present method has better processing performance. On the basis of satisfying the coating operation, the solid content of the positive electrode slurry can be significantly increased, which is beneficial to prevent the occurrence of undesirable phenomena such as cracking.
[0111] Among them, by comparing the test results of Example 1 and Example 14, it can be seen that after the positive electrode active material and the conductive agent are treated with a double-bond-containing silane coupling agent based on the dispersant provided by the present invention, the peel strength and capacity retention rate of the electrode sheet can be improved.
[0112] By comparing the test results of Example 2 and Example 3, it can be seen that when the molecular weight of the dispersant is 20000~30000 g / mol, compared with adding the dispersant provided by the present invention to the positive electrode active material and the conductive agent treated with a double bond-containing silane coupling agent at the same time, first adding the dispersant to the conductive agent treated with a double bond-containing silane coupling agent and then adding the positive electrode active material treated with a double bond-containing silane coupling agent can improve the peel strength and capacity retention rate of the electrode sheet.
[0113] By comparing the test results of Example 4 and Example 5, it can be seen that when the molecular weight of the dispersant is 2000~10000 g / mol, compared with adding the dispersant provided by the present invention to the positive electrode active material and the conductive agent treated with a double bond-containing silane coupling agent at the same time, first adding the dispersant to the positive electrode active material treated with a double bond-containing silane coupling agent and then adding the conductive agent treated with a double bond-containing silane coupling agent can improve the peel strength and capacity retention rate of the electrode sheet.
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A positive electrode slurry, characterized in that: The invention comprises a positive electrode active material, a conductive agent and a dispersant, wherein the dispersant is composed of a polymer segment and an anchoring group, the polymer segment is an acrylate-polyol unit, and the anchoring group comprises one or more of a nitrile group, an amide group, an ester group, a carboxyl group and a hydroxyl group; The molecular weight of the dispersant is 2000-30000 g / mol; the terminal group of the dispersant is an acrylate group; The dispersant is obtained by reacting a raw material composition comprising an acrylate-polyol monomer and an anchor group-containing monomer; the mass ratio of the anchor group-containing monomer to the acrylate-polyol monomer is (10-50):(30-90); The surface of the positive electrode active material is modified with a silane coupling agent containing a double bond; and / or the surface of the conductive agent is modified with a silane coupling agent containing a double bond.
2. The positive electrode slurry according to claim 1, characterized in that The acrylate-polyol monomer contains two or more acrylate groups, and / or the anchor group-containing monomer contains one or more of a nitrile group, an amide group, an ester group, a carboxyl group and a hydroxyl group.
3. The positive electrode slurry according to claim 1, characterized in that The acrylate-polyol monomers include one or more of poly(ethylene glycol) diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, and poly(propylene glycol) dimethacrylate; And / or, the anchor group-containing monomer includes one or more of acrylonitrile, methacrylonitrile, acrylamide, bisacrylamide, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, lauryl acrylate, isobutyl acrylate, tert-butyl acrylate, octadecyl acrylate, phenyl methacrylate, n-hexyl acrylate, and stearic methacrylate.
4. The positive electrode slurry according to claim 1, characterized in that: The silane coupling agent containing double bonds includes one or more of (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane, 3-(trimethoxysilyl)propyl acrylate, vinyltrimethoxysilane, and allyltrimethoxysilane.
5. A secondary battery, characterized in that: The invention comprises a negative electrode sheet, an electrolyte and a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer arranged on at least one side of the positive electrode current collector, and the positive electrode material layer is prepared by the positive electrode slurry according to any one of claims 1 to 4.
Citation Information
Patent Citations
Composition for electricity storage devices, slurry for electricity storage device electrodes, electricity storage device electrode, and electricity storage device
CN112385063A
Lithium iron phosphate positive electrode, preparation method and battery comprising lithium iron phosphate positive electrode
CN115172674A
Dispersant composition for electricity storage device electrode
CN116390976A
Conductive slurry for enhancing peel strength, pole piece and preparation method of slurry
CN117594287A
Copolymer for separator, and secondary battery comprising same
US20240030550A1